Charge and Discharge Reactions of a Lead Fluoride Electrode in a Liquid‐Based Electrolyte for Fluoride Shuttle Batteries:‐The Role of Triphenylborane as an Anion Acceptor‐. Issue 19 (23rd May 2019) - Konishi, Hiroaki; Minato, Taketoshi; Abe, Takeshi; Ogumi, Zempachi
Abstract: Lead fluoride (PbF2 ) is a promising electrode material for fluoride shuttle batteries (FSBs) owing to its high theoretical capacity (219 mAh g –1 ). In this study, the discharge and charge capacities of a PbF2 electrode were measured using a bis[2‐(2‐methoxyethoxy)ethyl] ether containing cesium fluoride and triphenylborane as an electrolyte. A high specific capacity was maintained during both the discharge and charge processes in the first cycle, but the capacity decreased from the first charge process to the following discharge process. To clarify the electrochemical reaction mechanism, the dissolution and change in the electronic state of Pb at the PbF2 electrode during the discharge and charge processes were evaluated via atomic absorption spectrometry (AAS) and X‐ray photoelectron spectroscopy (XPS). The results obtained from AAS and XPS indicated that Pb was formed during the discharge process. Conversely, the formation of PbF2 and dissolution of Pb coexisted within the wide range of charge process. The PbF2 could react in the following cycle, but the dissolved Pb was unable to contribute to the following discharge/charge reaction. Therefore, after the initial charge process, the capacity decreased. Abstract : Electrochemical measurement of PbF2 electrode for fluoride shuttle battery was performed in an electrolyte comprising G4, CsF, and TPhB. Initial discharge/charge capacities were high, but capacities were decreased in the following cycle. Analysis results indicate that Pb was formed during discharging, but PbF2 formation and Pb dissolution coexisted during charging. The capacity degradation was caused by lack of active material due to Pb dissolution.